Estimativa do tempo de produção de chorume em aterro controlado por meio de medidas de resistividade elétrica - Moreira, César Augusto [UNESP]; Braga, Antonio Celso De Oliveira [UNESP]; Hansen, Marco Antonio Fontoura (Sociedade Brasileira de Geologia, 2011)
Landfill is an engineering work that aims at to accommodate residues in the smallest possible space in the soil, with minimum damages to the environment and the public health. One in the constructive forms of a controlled landfill is the excavation of ditches with appropriate dimensions, for disposition of solid residues without compactation or impermeabilization. Liquid effluents generated for similar volumes of residues, disposed in ditches with ages different from closing, it should result in physical and chemical alterations you correlated at the time of residence materials. With base in this hypothesis, measures of electric resistivity were accomplished through the of Eletrical Resistivity geophysical method, on residues ditches closed annually between 12/2001 and 12/2007, localized in control landfill of the Cordeirópolis city (SP). The leachate is a liquid effluent generated by the decomposition of organic matter and characterized by high content in total dissolved solids, whose interaction with geological environment results in alterations in terms of electrical resistivity susceptible to detection for the geophysical instrumental. The results suggest a resistivity reduction for leachate percolation produced for ditches recently and increase progressive of the resistivity for older ditches. The statistical comparative analysis with reference values for the area suggests ages of the finish production and percolation leachate for soil and rock below the ditches.

Aterro é uma obra de engenharia que objetiva acomodar resíduos no menor es paço possível no solo, com danos mínimos ao ambiente e à saúde pública. Uma das formas construtivas de um aterro controlado é a escavação de valas com dimensões apropriadas, para disposição de resíduos sólidos sem compactação ou impermeabilização. Efluentes líquidos gerados por volumes de resíduos semelhantes, dispostos em valas com idades distintas de fechamento, devem resultar em alterações físicas e químicas correlacionáveis ao tempo de residência dos materiais. Com base nesta hipótese, foram realizadas medidas de resistividade elétrica por meio do método geofísico da Eletrorresistividade, sobre valas de resíduos fechadas anualmente entre 12/2001 e 12/2007, localizadas no aterro controlado do município de Cordeirópolis (SP). O chorume é um efluente líquido gerado pela decomposição de matéria orgânica e caracterizado pelo elevado conteúdo de sais dissolvidos, cuja interação com ambiente geológico resulta em alterações em termos de resistividade elétrica passíveis de detecção pelo instrumental geofísico. Os resultados sugerem uma redução da resistividade por percolação de chorume produzido em valas recentes e aumento progressivo da resistividade para valas mais antigas. A análise estatística comparativa com valores de referência para a área sugere idades de término da produção e percolação de chorume para solo e rocha abaixo das valas.
Time estimative of the leachate production in control landfill by electrical resistivity measuring
Keywords: monitoring; VES; leachate; waste; monitoramento; SEV; chorume; lixo